Tetrahedral grid generation for supercomputer modeling of flow past aerospace objects - Ermakov, M.K. (Numerical Methods and Programming (Vychislitel'nye Metody i Programmirovanie), 2020)
Gmsh open source software is used to generate ultra-detailed tetrahedral grids of up to 1 billion cells. The package allows one to build automatically specified grids on a PC in parallel OpenMP mode in a time not exceeding 1 hour when using an Intel i7–9700K PC. The experience of using the package to construct the spatial grids for problems of flows past aerospace objects is described. Several examples of supercomputer calculations for the flows past aerospace objects are given.